Feeding effects of total mixed ration on rumen metabolic profile in Cattle - Jahan, R; Amin, MR; Sarker, NR; Kamal, MT (Bangladesh Journal of Animal Science, 2018)
A feeding trial was undertaken to select the best combination of roughage and concentrate based on total mixed ration (TMR), to better rumen environment and determine the feeding effects of TMR on rumen metabolic profile in cattle. The experiment was conducted at Bangladesh Livestock Research Institute (BLRI) for a period of 35 days. A total of 5 types of TMR was prepared on fed basis with different roughage and concentrate ratios as T1=70:30, T2=60:40, T3=50:50, T4=40:60, and T5=30:70. Five cannulated bulls with an average live weight ranging from 200 to 300 kg and approximately 18 months of age were selected for the experiment. The present study indicated that there was no significant difference in pH among different treatment groups. Concentration of total volatile fatty acids (TVFAs) was highest in T2 group which was found to be increased up to 12 h after feeding, then gradually decreased up to 24 h. Concentration of total nitrogen (TN), ammonia nitrogen (NH3-N), non protein nitrogen (NPN) and protein nitrogen (PN) were highest in T5 group. Concentration of total nitrogen (TN), ammonia nitrogen (NH3-N) and protein nitrogen (PN) were gradually decreased up to 12 h after feeding but then gradually increased trend observed up to 24 h. Concentration of non protein nitrogen (NPN) was found to be decreased gradually from 0 h up to 24 h after feeding. The result also indicated that rumen NH3-N was positively correlated with TN intake of the animal. It can be concluded from the present study that the TMR provided better rumen environment at different hours of digestion could be used for better rumen fermentation. The best combination of roughage to concentrate ratio (30:70) was in T5 group for better N utilization to achieve maximum performance through proper feeding which might reflect the gross return of cattle production. Bang. J. Anim. Sci. 2018. 47 (1): 35-39